Capital structure effect on profitability during oil crisis: focusing on debt utilization on construction sector in Bursa Saham Malaysia / Mohamad Syairazy Mohd Sheh - Mohd Sheh, Mohamad Syairazy (2017)
This study used capital structure focus on leverage as an independent variable namely Long-term debt (LTD), total debt (TD) and Return on Asset (ROA) as firm Performance. This study is to investigate the relationship of capital structure focus on leverage towards the performance of the firm and which of the leverage contribute the most towards firm performance. The sample of this study taken yearly from 2006 to 2012. The findings shows that there is negative insignificant relationship between Long-Term Debt and Firm Performance. Next, there is a negative significant relationship between Total Debt towards Firm Performance. Panel data consist of secondary data gathered Malaysia firm have been used as study which employed Panel Regression Random Effect Model. Researcher use Econometric view 9 (E-Views 9) as medium to analyse and interpret descriptive, normality and regression. Lastly, researcher have come out with the conclusion and recommendation about the research that can be done in the further.